Analisa Waktu Buka-Tutup Pintu Lift: Gedung KH Mas Mansyur Universitas Muhammadiyah Palembang - Ramandika, Bagus; Mafra, Ramadisu (Universitas Muhammadiyah Palembang, 2024)
As an important element in a vertical transportation system, lift doors play a crucial role in the lift's overall performance. Limited time for opening and closing doors can affect the flow rate of passengers, reducing the efficiency of using the elevator. This research aims to analyze the time required by the system for the lift door opening and closing process which will be explained using quantitative descriptive methods. The research method utilizes the time motion method with video recording system technology tools during the process of opening and closing the elevator doors in the KH Mas Mansyur Building, Kampung B, Muhammadiyah University, Palembang. For six days, the research was carried out during the busiest hours. The research results are expected to provide an in-depth understanding of the variables that influence door opening and closing times, such as door speed, passenger detection, and security mechanisms. The research results show that in fact the average time for the lift door opening and closing process in the